Cleavage of E-Cadherin by Matrix Metalloproteinase-7 Promotes Cellular Proliferation in Nontransformed Cell Lines via Activation of RhoA. (10th May 2010) - Lynch, Conor C.; Vargo-Gogola, Tracy; Matrisian, Lynn M.; Fingleton, Barbara
Abstract : Perturbations in cell-cell contact machinery occur frequently in epithelial cancers and result in increased cancer cell migration and invasion. Previously, we demonstrated that MMP-7, a protease implicated in mammary and intestinal tumor growth, can process the adherens junction component E-cadherin. This observation leads us to test whether MMP-7 processing of E-cadherin could directly impact cell proliferation in nontransformed epithelial cell lines (MDCK and C57MG). Our goal was to investigate the possibility that MMP-7 produced by cancer cells may have effects on adjacent normal epithelium. Here, we show that MMP-7 processing of E-cadherin mediates, (1) loss of cell-cell contact, (2) increased cell migration, (3) a loss of epithelial cell polarization and (4) increased cell proliferation via RhoA activation. These data demonstrate that MMP-7 promotes epithelial cell proliferation via the processing of E-cadherin and provide insights into the molecular mechanisms that govern epithelial cell growth.